Conspiracy Theories in the Core of Discussion about COVID-19 - Melkonyan, Viktorya (YSU Journal of International Affairs, 2022)
Partially justified, intentionally directed and unreliable conspiracy theories are real challenges on the way to control and overcome modern crises. In parallel, the role of information technologies is growing in the all spheres of human lives, which means that the quality of information and technologies predetermines the quality of human resources, accordingly also the level of development of modern societies and the perspectives of their future evolution. The brilliant example may serve actively disseminated disinformation along with conspiracy theories in time of Covid-19, which is linked to different international and local actors. The article discusses the theory and practice of anti-scientific conspiracy theories and stresses the negative influence of such theories on formation of public thinking and direction of public behavior.
Keywords: coronavirus; disinformation; conspiracy theories; information; social media; international politics